Which criteria characterize a health literate health care organization? - a scoping review on organizational health literacy - Daniel Bremer; Izumi Klockmann; Leonie Jaß; Martin Härter; Olaf von dem Knesebeck; Daniel Lüdecke (BMC, 2021)
Abstract Background Organizational health literacy (OHL) aims to respond to the health literacy needs of patients by improving health information and services and making them easier to understand, access, and apply. This scoping review primarily maps criteria characterizing health literate health care organizations. Secondary outcomes are the concepts and terminologies underlying these criteria as well as instruments to measure them. Methods The review was carried out following the JBI Manual on scoping reviews. The databases CINAHL, Cochrane Library, JSTOR, PsycINFO, PubMed, Web of Science Core Collection, and Wiley Online Library were searched in July 2020. Three researchers screened the records and extracted the data. The results were synthesized systematically and descriptively. Results The literature search resulted in 639 records. After removing duplicates, screening by title and abstract, and assessing full-texts for eligibility, the scoping review included 60 publications. Criteria for OHL were extracted and assigned to six main categories (with 25 subcategories). The most prevalent topic of organizational health literacy refers to communication with service users. Exemplary criteria regarding this main category are the education and information of service users, work on easy-to-understand written materials as well as oral exchange, and verifying understanding. The six main categories were defined as 1) communication with service users; 2) easy access & navigation; 3) integration & prioritization of OHL; 4) assessments & organizational development; 5) engagement & support of service users, and 6) information & qualification of staff. The criteria were based on various concepts and terminologies. Terminologies were categorized into four conceptual clusters: 1) health literacy in various social contexts; 2) health literate health care organization; 3) organizational behavior, and 4) communication in health care. 17 different assessment tools and instruments were identified. Only some of the toolkits and instruments were validated or tested in feasibility studies. Conclusions Organizational health literacy includes a significant number of distinct organizational criteria. The terminologies used in the OHL literature are heterogeneous based on a variety of concepts. A comprehensive, consensus-based conceptual framework on OHL is missing.